STRATEGI GURU DALAM MENGENALKAN HURUF HIJAIYAH PADA ANAK USIA 5 – 6 TAHUN DI RA PERWANIDA 3 PALEMBANG - Pangestu, Maulana; Ali Murtopo; Aida Imtihana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to recognize Arabic letters (huruf hijaiyah) in early childhood is a fundamental skill that needs to be stimulated from an early age, as it forms the basis for reading the Qur’an and supports children’s language and cognitive development. Observations at RA Perwanida 3 Palembang show that children aged 5–6 years are already able to recognize, mention, read, and distinguish hijaiyah letters well, indicating that the learning process implemented by teachers has been effective and developmentally appropriate. This study aims to describe the strategies used by teachers in introducing hijaiyah letters and to identify the supporting and inhibiting factors in the learning process. This research uses a qualitative method with a case study approach, and data were collected through in-depth interviews, participatory observation, and documentation of learning activities. The results show that teachers apply varied and engaging learning strategies through play-based approaches such as singing, storytelling, and routine repetition, as well as using the Iqro method and listening–visual techniques. Teachers also utilize various learning media such as hijaiyah flashcards, hijaiyah puzzles, Iqro books, and visual materials to improve children’s engagement and understanding. Supporting factors include adequate learning facilities, parental involvement, and children’s enthusiasm during learning activities. Meanwhile, inhibiting factors involve irregular attendance, individual differences in ability, noisy classroom conditions, and children’s fluctuating concentration. This study concludes that creative and contextual learning strategies are effective in improving children’s ability to recognize hijaiyah letters; however, improvements are needed in attendance consistency and attention management to optimize learning outcomes.